Preoperative atorvastatin reduces bleeding and blood transfusions in patients undergoing elective isolated aortic valve replacement. (11th February 2019) - Nenna, Antonio; Spadaccio, Cristiano; Lusini, Mario; Nappi, Francesco; Mastroianni, Ciro; Giacinto, Omar; Pugliese, Giuseppe; Casacalenda, Adele; Barbato, Raffaele; Barberi, Filippo; Greco, Salvatore Matteo; Satriano, Umberto; et al.
Abstract: OBJECTIVES: Minimization of bleeding to reduce the use of blood products is of utmost importance in cardiac surgery. Statins are known for their pleiotropic effects beyond lipid-lowering properties, and the use of atorvastatin preoperatively is associated with reduced risk of bleeding and blood product use after coronary surgery. However, no studies have investigated if this beneficial effect also extends to aortic valve surgery. METHODS: In this retrospective cohort study, 1145 consecutive patients undergoing elective primary isolated aortic valve replacement meeting the inclusion and exclusion criteria were selected from January 2009 to December 2017 (547 in the atorvastatin group, 598 in the control group). Postoperative bleeding, blood product use, and complications were monitored during hospitalization. RESULTS: Postoperative bleeding was significantly lower in the atorvastatin group compared with the controls in the first 12 h after surgery (372 ± 137 vs 561 ± 219 ml; P = 0.001) and considering overall bleeding (678 ± 387 vs 981 ± 345 ml, P = 0.001). A total of 32.3% of controls and 26.3% of atorvastatin users received packed red blood cells ( P = 0.027), and major surgical complications were similar between the groups. Postoperative length of stay was shorter in the atorvastatin group with an average reduction of 1 day of hospitalization (6.0 ± 1.4 vs 6.9 ± 2.1 days; P = 0.001). Postoperative bleeding among the atorvastatin-treated patients was significantly greater in those taking lower doses compared to those taking higher doses of atorvastatin with a 20% between-group difference ( P = 0.001). CONCLUSIONS: Preoperative treatment with atorvastatin might reduce postoperative bleeding and transfusion of packed red blood cells in patients undergoing elective isolated aortic valve replacement. This result might translate into faster recovery after surgery and reduced hospitalization costs.